Uji Evektifitas Eksudat Akar Bangun – Bangun (Coleus amboimicus) untuk Menghambat Pertumbuhan Jamur Akar Putih (Rigidoporus micropus) di Laboratorium - irfansyah harahap; Lisnawita Lisnawita; Suzanna F Sitepu (Jurnal Agroekoteknologi, 2019)
The white root rot disease caused by Rigidoporus micropus is the main disiase found in rubber trees that can cause decay on the roots. The research begins from April until August, 2016. It was conducted in Laboratorium Proteksi Balai Pembibitan Karet Sungai Putih Laboratory of Protection of Rubber Breeding Center, Deli Serdang District, North Sumatera Province. The objective of the research was to find out the potentials of root exudates to inhibit the growth of R. microporus. This research used non-factorial RAL (Completely Randomized Design) which observed the growth area of colony of R. microporus, hypha abnormality, inhibition percentage, protein analysis as well as hypha microscopy and macroscopy. In this study it was found that protein compounds were not inhibiting factors for growth of white root fungi but phenol compounds. The largest growth of R. microporus colony was found in the control treatment (64 cm2). Meanwhile, the lowest growth of R. microporus colony was found in the treatment of 10% of bangun-bangun root exudates. This research proves that bangun-bangun root exudates were able to inhibit the growth of white root rot disease of rubber. Hypha abnormality was found in every treatment which has been added by bangun-bangun root exudates. However, abnormalities of white root fungal hyphae were clearly seen in the treatment 10% of bangun-bangun of root exudates.